The Legal Certainty of Medical Malpractice in Relation to Working Hour Violations - Ikhsan, M.; Lany, Arman (Research Horizon, 2025)
The medical profession faces significant legal risks related to malpractice allegations, partly driven by physician fatigue resulting from excessive working hours. In Indonesia, the absence of specific regulations on maximum working hours for physicians creates legal uncertainty and tends to place full responsibility on individual practitioners. This study aims to analyze the legal certainty afforded to doctors in malpractice cases associated with work-related fatigue and violations of working hour standards based on prevailing laws and regulations. Using a normative juridical method with a literature study approach, the research examines secondary data consisting of primary legal materials, including the 1945 Constitution, Law Number 6 of 2023 on Job Creation, and Law Number 17 of 2023 on Health, along with secondary legal materials analyzed qualitatively. The findings show that although no explicit working hour regulations for physicians exist, legal protection can still be grounded in current laws. The Manpower Law provides standard working hour guidelines, while the Health Law obliges healthcare facilities to ensure the safety and well-being of medical personnel. Therefore, legal responsibility for malpractice caused by fatigue due to excessive work systems should not rest solely on individual physicians but may also be attributed to healthcare institutions as employers.